Requirements and special considerations for drug trials with children across six jurisdictions: 1. Clinical trial application review in the regulatory approval process - Stewart, Breanne; Lepola, Pirkko; Egger, Gunter F.; Ali, Fahimeda; Allen, Albert J.; Croker, Alysha K.; Davidson, Andrew J.; Dicks, Pamela; Faust, Saul N.; Green, Dionna; Hovinga, Collin; Klein, Agnes V.; et al. (Frontiers in Medicine, 2025)
BackgroundConducting clinical trials (CTs) with children presents several challenges. A major challenge is the need to enrol participants at multiple sites across different jurisdictions. Regardless of whether the trials involve children, adults, or both, CTs need to meet separate Competent Authority (CA) requirements to proceed in each participating country. This work, undertaken by the Working Group (WG) on International Collaborations at the European Network of Pediatric Research at the European Medicines Agency (Enpr-EMA) aims to describe the regulatory requirements including any specific to pediatrics, as well as current or upcoming changes across six jurisdictions—the European Union (EU), United Kingdom (UK), United States of America (USA), Canada, Japan, and Australia.MethodsAn open questionnaire developed by the WG and directed at both the CA and the national pediatric clinical trial networks arranged by jurisdictions.ResultsA synopsis of the current legislative and regulatory requirements for CTs applications, application submission processes and application requirements is presented for each of the six jurisdictions. Requirements were found to be mostly consistent across jurisdictions. No difference was found in processes for CTs submission, review, and authorization for pediatric CTs vs. CTs in adults. However, there are additional Ethics Committee/Institutional Review Board requirements for clinical trials including children. Some jurisdictions are considering adopting a risk-based approach, inspired by the Organization of Economic Co-operation and Development (OECD) recommendations on Governance. Changes currently or soon to be implemented in some jurisdictions are also described.ConclusionsRegulators from the jurisdictions represented in this WG are collaborating to facilitate regulatory harmonization and foster international alignment of pediatric CTs. By interacting with their respective regulatory bodies and developing expertise in their jurisdiction's regulatory requirements, national pediatric networks can support both academic and industry sponsors in navigating the regulatory process for CTs.